The importance of the media in the field of education: Educational television for example - Ashna Shawkat Hadi; Azad Ramazan Ali (QALAAI ZANIST JOURNAL, 2024)
The media plays a positive role in the education process. Education through the media is related to preparing the media worker to conduct the education process.This requires coordination of society’s values ​​and goals and effective participation between journalists and educators in order to meet the needs of individuals, because various media play a role in the socialization process, because they disseminate information and adapt ideas in all areas They raise their values ​​and beliefs and adapt them to new situations according to their students’ desires.Media and education are two pillars.The state must plan for them to be successive demonstrators, play an active role in society, and properly guide them in social behaviors that are acceptable, especially those that are acceptable and useful to our society See the close relationships he has with individuals in society.There is no doubt that the media is an important tool of communication, with the aim of conveying information and ideas through various means to facilitate the public, in order to influence and direct them or serve them on a particular subject educational television is one of the media in the Kurdistan Region, which is supervised by the Ministry of Education.Educational television may originate within the educational institutions themselves, so it is run by a private administration.